Normalisering av droger bland gymnasieelever i Malmfälten : En kvantitativ undersökning - Rynbäck, Emma (2015)
The study is based on a quantitative approach. The aim of the study is to clarify whether there is a tendency to normalization of drugs in general, and cannabis in particular among high school students in Malmfälten and if there are various risk and protective factors in relation to the normalization. The data used in the study is based on existing questionnaires answered by high school students in northern Sweden in 2012 and 2014. To analyze the data previous research of the normalization and how to categorize young people from their drug use has been used. The theory of social ties has also been used. The results show that cannabis was the most common drug to be offered and to try in both Malmfälten and in the rest of Norrbotten. It was more common to be offered, try and use regular different kinds of drugs in Norrbotten in comparison to Malmfälten. Between 2012 and 2014 rates fell among those who claimed to have tried and used different kinds of drugs regularly. Regarding the regular use, hard drugs where more common in 2012 and internet drugs in 2014. Between 2012 and 2014, the percentage of students with restrictive attitudes decreased, while the percentage with neutral- and liberal attitudes increased. Students with liberal attitudes had tried cannabis to the greatest extent. The student in Malmfälten that most likely had tried cannabis was a boy, in a practical training, in grade 3. The boy had a liberal attitude, limited knowledge, and did not live with his parents. He had poor childhood conditions and had friends who used cannabis. He used alcohol and tobacco. Background factors that influenced the likelihood to try cannabis most was the attitude to drugs and friends use of cannabis. Validerat; 20151216 (global_studentproject_submitter)